2001
DOI: 10.1128/iai.69.12.7635-7641.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin and Lipopolysaccharide Influence Phagocytosis ofBordetella pertussisby Human Monocytes

Abstract: The potential of human monocytes to mediate the clearance of Bordetella pertussis infection was examined. Bacteria expressing green fluorescent protein were incubated with adherent peripheral blood monocytes, and phagocytosis was quantified by using fluorescence microscopy. Monocytes internalized only a small percentage of the adherent bacteria. Surface-associated Bvg-regulated virulence factors, including adenylate cyclase toxin and filamentous hemagglutinin, did not affect attachment or phagocytosis. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
4
26
1
Order By: Relevance
“…7). As observed in previous studies with human peripheral blood monocytes (33), phagocytosis of unopsonized B. pertussis by rat alveolar macrophages was relatively inefficient, with less than one internalized bacterium per monocyte when experiments were conducted at an MOI of 5 (Fig. 7).…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…7). As observed in previous studies with human peripheral blood monocytes (33), phagocytosis of unopsonized B. pertussis by rat alveolar macrophages was relatively inefficient, with less than one internalized bacterium per monocyte when experiments were conducted at an MOI of 5 (Fig. 7).…”
Section: Resultssupporting
confidence: 50%
“…7). Phagocytosis of B. pertussis by monocytes (33) and macrophages (Fig. 3) appears to be inherently inefficient, and resistance to phagocytosis does not cor- It was previously reported that wild-type LPS of B. pertussis is resistant to binding, aggregation, opsonization, and permeabilization by SP-A (32).…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment of human monocytes with purified pertussis toxin, an inhibitor of G-proteins, blocks the ability of monocytes to internalize wild-type bacteria (Schaeffer and Weiss, 2001). Similar inhibitory effect was also reported for okadaic acid (Stromhaug et al, 1997;Pahan et al, 1998), the inhibitor of serine/threonine protein phosphatases PP1 and PP2A.…”
Section: Intracellular Signalsmentioning
confidence: 99%
“…However, studies addressing the abilities of monocytes and neutrophils to phagocytose B. pertussis have suggested that evasion of phagocytes, rather than intracellular survival, allows bacterial cells to escape the effector cells of innate immunity (38,45).…”
mentioning
confidence: 99%
“…iMDDC (10 6 /ml) were resuspended in complete medium without penicillin and streptomycin (referred to below as Bp medium) and then infected with B. pertussis cells at bacterium-to-cell ratios of 20:1 and 100:1. iMDDC and bacteria were centrifuged for 2 min at 640 ϫ g to facilitate contact (38) and then incubated for 2 h at 37°C under 5% CO 2 . Cells were then extensively washed and incubated for 3 h in Bp medium in the presence of polymyxin B (20 g/ml) to kill adherent extracellular bacteria.…”
mentioning
confidence: 99%